The Development and Initial Validation of the Youth Sexual Intention Scale: Indonesian Version - Rahmi Lubis; Zahrotur R. Hinduan; Ratna Jatnika; Baydhowi Baydhowi; Hendriati Agustiani (SAGE Publishing, 2022)
Interventions for the early sexual problem in adolescents require proper measurement of sexual intentions. The adolescent sexual intention scales have been widely used by researchers in the West. However, those scales are not very suitable for adolescents in eastern cultures such as Indonesia. As a religious society, Indonesian people have different sexual expectations from liberal western society. Religious teachings and societal norms shape sexual beliefs that reflect semi-restrictive sexual socialization. Thus, sexual intention measurement that represents the sexual beliefs of the subject under study becomes important. Therefore, this two-steps study aims to develop and validate the Youth Sexual Intention Scale (YSIS). In the first step, qualitative elaboration resulted in 27 themes of adolescent sexual beliefs, which turned into 31 items according to the Theory of Planned Behavior (TPB). In the second step, we selected 396 students using the cluster random sampling technique. We investigated 2 methods of validity, content validity using CVI and construct validity using confirmatory factor analysis (CFA). The content validity examination proved that all scale items had high validity (CVI = .93). Meanwhile, the CFA showed that the data was fit for the model (Chi-square 819,420, P <.001, RMSEA = .056, CFI = .978, TLI = .972). The CFA groups items into 4 dimensions, namely, sexual attitudes, subjective norms, perceived behavioral control, and sexual intentions. The reliability test shows an Alpha coefficient of .854. We conclude that 26-items YSIS is a valid and reliable instrument to measure belief-based youth sexual intentions (15-18 years) in religious culture.